Slang Words Used in Fast X Movie - I Gusti Ngurah Surya Bhaskara Pasimpangan; Ni Luh Putu Krisnawati; Novita Mulyana (CV. Ulil Albab Corp, 2024)
This research entitled Slang Words Used in Fast X Movie. The aims of this study are identify the types of slang words and functions of slang words used in Fast X Movie. This research using descriptive qualitative method. The data was obtained from movie subtitle spoken by the characters in Fast X Movie. The data was collected using documentation with note-taking method. This research using informal method to present the data. The theories used in this research are type of slang words proposed by Yule (2010) and function of slang words proposed by Allan and Burridge (2006). After finding the data, the result showed that there are seven types found in Fast X Movie, namely compounding, blending, clipping, coinage, borrowing, derivation, and multiple process. Moreover, the functions of slang word were analysed and found that four functions of slang used by character in Fast X Movie, namely to address, to reveal anger, to express impression, and to initiate relax conversation.